Risk Management Implementation and Business Continuity in Private Higher Educational Institutions - Mani Maaran, Krishnan (2024)
This study is looking into the aspect of risk management implementation and business continuity in private higher education institutions. Private higher education in Malaysia has been growing rapidly since late 80’s and it has provided an alternative for students to pursue their tertiary study of choice. Every year new private higher education institutions are established; competition gets keener and the challenge to continue existing is becoming greater. The ever-challenging private higher education business environment challenges private higher education institution to stay afloat like any other business, but the decision to cease operation of a private higher education institution is having serious and detrimental effect on various stake holders unlike other business. It is known fact that any untoward happenings to private higher education institution will have direct impact to students and their future. The fluctuating number of private higher education institution in operation year after year is having wholesome impact to the nation as well. The readiness of private higher education institution in facing business uncertainty and continue to exist is critical. This study adopts a qualitative method approach supported with analysis from data collected through quantitative method as well. Top executives of selected private higher education institutions were interviewed, and a survey questionnaire was distributed to selected private higher education employees for related data gathering. The study revealed private higher education institution agrees and knows the importance of risk management; risk and risk management knowledge are lacking among the process owners in private higher education institutions; organizational culture plays crucial role in effective implementation of risk management; risk management and business continuity have a real and inevitable link; having a sector specific risk management framework will further strengthen and benefit the private higher education institutions in managing risks faced in their higher education business. There are several limitations in this study which are; only private higher education institutions located in Klang Valley were included, these institutions should have been operating more than ten years with more than 300 students and it must be a homegrown private higher education institution.